K.H. Daud Ismail and His Writing on Qur'anic Interpretation in Buginese Language - M. Hamdar Arraiyyah (Center for Research and Development of Religious Literature and Heritage, 2012)
This article introduces on ulama or a Muslim scholar of South Sulawesi Province in Indonesia. His name is Kiyai Haji Daud Ismail (d. 2006). He belonged to Buginese ethnic. Though he had a very limited chance to attend formal education, he succeded to gain an ·excellent mastery of Arabic and Islamic teaching. His writing on Qur’anic interpretation became a valuable work for Buginese people and lndonesian Muslims as well. The work communicates the messages of Muslim's scripture and gives guidance to translate and explain the Qur'anic verses in Buginese language. It also functions to strengthen the use and the position of the related local language compared with the other languages in Indonesia and an over the world.